Synthesis and characterization of novel 4-benzyloxyphenyl 4-[4-(n-dodecyloxy) benzoyloxy]benzoate liquid crystal - Balkanli, Emine; Cakar, Fatih; Ocak, Hale; Cankurtaran, Ozlem; Bilgin Eran, Belkiz (Tubitak Scientific & Technological Research Council Turkey, 2021)
Liquid crystal (LC) compound 4-Benzyloxyphenyl 4-[4-(n-dodecyloxy)benzoyloxy]benzoate (BDBB) was prepared and characterized. Inverse gas chromatography (IGC) was to be a beneficial analysis method for the research of thermodynamic characteristics of the new LC. Acetate and alcohol isomers were used to examine LC selectivity via the IGC technique at temperatures between 333.2 K and 483.2 K. The retention diagrams of n-heptane, n-octane, n-nonane, n-decane, undecane, dodecane, tridecane, n-butyl acetate, isobutyl acetate, ethyl acetate, n-propylbenzene, isopropylbenzene, ethylbenzene, chlorobenzene, and toluene on BDBB were plotted with temperatures of 483.2-493.2 K. Flory-Huggins interaction parameter and weight fraction activity coefficient at infinite dilution were researched for BDBB.
Keywords: Inverse gas chromatography; liquid crystals; thermodynamics; MESOMORPHIC PROPERTIES; SURFACE; BEHAVIOR; DESIGN; Chemistry; Engineering